Prediction of resistance to TiLV in the selection of parents for G20 - Mahmuddin, Mahirah; Hamilton, Matthew (2024)
Prediction of resistance to natural tilapia lake virus (TiLV) in the selection of parents for G20 including EBVs for challenge test survival and allele counts for QTL for TiLV natural (i.e. immersion) resistance.